Aorto-Right Atrial Fistula after Minimally Invasive Tricuspid Valve Repair: A Report of Two Cases - Ishidou, Kouhei; Hirofuji, Aina; Wakabayashi, Naohiro; Kamiya, Hiroyuki (The Thoracic and Cardiovascular Surgeon Reports, 2020)
We experienced two cases of postoperative iatrogenic aorto-right atrial fistula (ARAF) after tricuspid valve repair (TVR) using minimally invasive cardiac surgery (MICS) technique. In both the cases, the flow of ARAF passed through the sinus of Valsalva near the noncoronary cusp (NCC)/right coronary cusp (RCC) commissure or NCC to right atrium. The quality of the fine needle used in the MICS technique may be inferior to that used in conventional surgery; ARAF after TVR could be a unique pitfall with the MICS technique.
Keywords: minimally invasive cardiac surgery; aorto-right atrial fistula; tricuspid valve repair